2007
DOI: 10.1124/mol.107.041764
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Protein B1 Is an Activator of Apoptotic Response to Antimetabolite Drugs

Abstract: We explored the role of a chromatin-associated nuclear protein high mobility group protein B1 (HMGB1) in apoptotic response to widely used anticancer drugs. A murine fibroblast model system generated from Hmgb1 ϩ/ϩ and Hmgb1 Ϫ/Ϫ mice was used to assess the role of HMGB1 protein in cellular response to anticancer nucleoside analogs and precursors, which act without destroying the integrity of DNA. Chemosensitivity experiments with 5-fluorouracil, cytosine arabinoside (araC), and mercaptopurine (MP) demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…Furthermore, we demonstrate that diabetes upregulates PARP-1 and caspase-3 expression in the retinas and that administration of glycyrrhizin attenuates diabetes-induced PARP-1 and caspase-3 upregulation. Consistent with our findings, previous studies demonstrated that HMGB1 overexpession induces PARP-1 and caspase-3 expression [23,36] and that glycyrrhizin attenuates apoptosis induced by ischemia-reperfusion injury in rat brains [15]. Our findings suggest that the mechanism by which glycyrrhizin prevents diabetes-induced PARP-1 and caspase-3 expression in the diabetic retina could be through lowering ROS generation.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we demonstrate that diabetes upregulates PARP-1 and caspase-3 expression in the retinas and that administration of glycyrrhizin attenuates diabetes-induced PARP-1 and caspase-3 upregulation. Consistent with our findings, previous studies demonstrated that HMGB1 overexpession induces PARP-1 and caspase-3 expression [23,36] and that glycyrrhizin attenuates apoptosis induced by ischemia-reperfusion injury in rat brains [15]. Our findings suggest that the mechanism by which glycyrrhizin prevents diabetes-induced PARP-1 and caspase-3 expression in the diabetic retina could be through lowering ROS generation.…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, HMGB1 could act either directly by interaction with the core telomerase subunits and/or indirectly via promotion of synthesis/folding of factor(s) participating in formation (assembly) of active telomerase (Collins 2008). The latter would be compatible with DNA microarrays revealing diminished expression of numerous heat shock proteins (chaperones) in HMGB1 −/− MEFs relative to the parental cells (Krynetskaia et al 2008), including Hsp90 mRNA as revealed by qRT-PCR (data not shown). Hsp90 protein has previously been shown to be an important factor in activation of telomerase (Holt et al 1999;Woo et al 2009).…”
Section: Discussionmentioning
confidence: 80%
“…Intracellular HMGB1 in general is an antiapoptotic protein in yeast and mammalian cells in response to several apoptotic stimuli such as ultraviolet radiation, CD95 or tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) ligation as well as Bax activation (2,54). In addition, gene chip microarray studies demonstrate that knockout of HMGB1 in mouse embryonic fibroblasts significantly impairs metabolic pathways, including those involved in fructose, mannose, galactose, glycolysis and purine metabolism (55). These findings suggest a role of HMGB1 in the regulation of mitochondrial structure and function.…”
Section: Hmgb1 and Autophagymentioning
confidence: 99%